Risk characterisation of chemicals of emerging concern in real-life water reuse applications - Jan C. Specker; Antonia Praetorius; Milo L. de Baat; Nora B. Sutton; Annemarie P. van Wezel (Environment International)
Water reuse is a viable option to address temporal or structural water shortages. However, the ubiquitous presence of chemicals of emerging concern (CECs) in natural systems, especially the aquatic environment, represents a significant obstacle to water reuse and the receiving environment. Therefore, an extensive literature review was performed to identify current water reuse practices at field scale, reported types and levels of CECs and their associated risks for human and environmental health. Treated wastewater was the primary reused water source, with agricultural reuse being the most frequently reported reuse application (28 %), followed by indirect-potable reuse (16 %). Contrary to potable reuse, it was observed that almost no studies applied additional treatment before water reuse for agricultural purposes. Based on calculated risk quotients, ecological risks were identified for perfluorooctanesulfonic acid, chlorpyrifos, triclocarban, and ethinylestradiol, and human health risks for perfluorooctanesulfonic acid and perfluorooctanoic acid. Environmental risks could be assessed for 77 % of detected CECs, while the human health risk assessment is limited to 28 %. For agricultural reuse, it was observed that CEC concentrations in produced crops were at acceptable levels. However, a thorough risk assessment of CECs during water reuse is currently limited due to a focus on a defined class of contaminants in the literature, i.e., pharmaceuticals, and falls short of per- and polyfluoroalkyl substances. Therefore, future water reuse studies should include a broader set of CECs and study additional mitigation options to decrease CEC concentrations before or during water reuse. Moreover, environmental harm caused by CECs during water reuse such as adverse effects on the microbial soil community or leaching to non-target sources has hardly been studied in the field and presents a knowledge gap.